Manajemen Pendidikan Inklusi di SMAN 1 Padangan - Nanda Rizki Wiliyanto (Mudir : Jurnal Manajemen Pendidikan, 2022)
Inclusive Education Management, In inclusive education institutions aim to provide opportunities for children with disabilities or special needs to be able to participate in learning like other normal children. Inclusive education management is an activity, planning, implementing, and supervising all activities (programs), in order to provide education for all students, including students with special needs in order to achieve goals. This type of research includes qualitative research and uses descriptive analysis techniques, in order to find out the problem and get accurate data, the researcher uses the method of observation, interviews and documentation. The results of this study can be said that in the discussion of inclusive education management that stands out is the emphasis on the management of inclusive education programs. that planning (planning) is a basic function of management, because in organizing, actuating, and controlling must first be planned. So that the risk borne is relatively small, all activities, actions, and policies should be planned in advance. Organizing The organizing function (organizing = division of labor) is closely related to the planning function, because organizing must be planned. Actuation is moving people to work in accordance with the tasks assigned to them so that they can achieve the goals that have been set. In carrying out the main tasks and functions given by superiors to subordinates or members, they must be carried out with a full sense of responsibility, totality, and maximum. There needs to be good cooperation from superiors to subordinates or members as well as among fellow members in carrying out tasks. So that the goals to be achieved can be realized. Controlling is an important part of management, because in supervision one will know if a program is running smoothly or if there is an obstacle. Supervision is trying as much as possible to oversee the programs that have been planned so that they run optimally and as they should.